Effect Of Tax, Tunneling Incentive, Bonus Mechanism And Profitability On Transfer Pricing - Satria, Friyan; Satria, Frinan; Andoko, Andoko (Program Pascasarjana STIE Amkop Makassar, 2023)
One of the most important sources of revenue for the state is taxation. Paying taxes is a legal obligation that must be met by both individuals and businesses. Transfer pricing is one method of reducing the tax burden. This, however, has the potential to reduce state revenue. The purpose of this research is to determine the impact of taxes, tunneling incentives, Bonus Mechanisms, and Profitability on transfer pricing in Indonesian manufacturing companies listed on the Indonesia Stock Exchange 2019 - 2022. Secondary data from 171 manufacturing companies listed on the Indonesia Stock Exchange is used in this study. Purposive sampling was used to select the sample, and the research sample contained as many as 24 companies. Researchers use the 2019-2022 time frame. According to the findings of the Smart PLS study, the tunneling incentive variable has a positive and significant effect on transfer pricing, while the profitability variable has a negative and significant effect on transfer pricing. Transfer pricing is unaffected by variable taxes and bonus mechanisms. Keywords: Tax, Tunneling Incentive, Bonus Mechanism, Profitability, Transfer Pricing.